Behavioral heterogeneity and financial markets: Locked/crossed quotes under informationally efficient pricing - Youzong Xu; Bo Li (Cogent Economics & Finance, 2017)
Market professionals and regulators have been concerned by locked/crossed quotes (negative quoted spreads) for years. To ease the concerns that locked/crossed quotes may cause confusion or instability in financial markets and to promote market efficiency, the Securities and Exchange Commission implemented rules that ban locked/crossed quotes. We consider a competitive financial market that does not contain the factors considered by market professionals and regulators consider as the origins of locked/crossed quotes. We find that if there are at least three types of traders in this financial market, locked/crossed quotes can arise naturally under efficient pricing. These locked/crossed quotes reflect information transmitted in financial markets, facilitating price discovery. Hence, regulations banning locked/crossed quotes are inappropriate, as these regulations may harm the efficiency of price discovery.
Keywords: 330; adverse selection; locked/crossed quotes; behavioral heterogeneity